Tri-modal ensemble for enhanced Bangla sign language recognition - Shams, Khan Abrar; Reaz, Md. Rafid; Islam, Sanjida; Rafi, Mohammad Ryan Ur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.